Age or age at onset? Which of them really matters for neuro and social cognition in schizophrenia?. Issue 1 (30th January 2015) - Linke, Magdalena; Jankowski, Konrad S.; Ciołkiewicz, Agnieszka; Jędrasik-Styła, Małgorzata; Parnowska, Dorota; Gruszka, Anna; Denisiuk, Mirella; Jarema, Marek; Wichniak, Adam
Abstract: In schizophrenia patients, both an older age and earlier age at onset of the disease are related to worse cognitive functioning. As patients with later schizophrenia onset are also older, analysing the two effects separately can be misleading, as they can either be spurious or cancel one another out. The purpose of the present study was to elucidate the effects of age and onset-age on cognition in schizophrenia patients. Individuals with schizophrenia ( N =151), aged 18–59 years, were examined with a MATRICS Consensus Cognitive Battery (MCCB) to get a full picture of their cognitive performance. Results showed age and age at onset indeed interrelated. Regression analyses revealed later onset of schizophrenia related to better social cognition. Patients׳ older age was related to a slower performance in symbol coding task, less effective executive functions, worse visual learning, lower attention, and lower total score in the MCCB. In the above regression analyses we controlled doses of antipsychotic medications. The results suggest that a previously found relationship between older age and social cognition might be spurious, and strengthen observations that it is specifically later onset-age which fosters better social cognition in schizophrenia patients. Highlights: The purpose of the present study was to elucidate the effects of age and onset-age on cognition in schizophrenia patients. We examinated 151 patients with schizophrenia with MATRICS Consensus Cognitive Battery. This is the first study considering age and age at onset together, controlling for their intercorrelation, and showing that the age at onset but not the age of the patient is important for social cognition.